Dosimetric effects caused by couch tops and immobilization devices: Report of AAPM Task Group 176. Issue 6 (27th May 2014) - Olch, Arthur J.; Gerig, Lee; Li, Heng; Mihaylov, Ivaylo; Morgan, Andrew
Abstract : The dosimetric impact from devices external to the patient is a complex combination of increased skin dose, reduced tumor dose, and altered dose distribution. Although small monitor unit or dose corrections are routinely made for blocking trays, ion chamber correction factors, e.g., accounting for temperature and pressure, or tissue inhomogeneities, the dose perturbation of the treatment couch top or immobilization devices is often overlooked. These devices also increase skin dose, an effect which is also often ignored or underestimated. These concerns have grown recently due to the increased use of monolithic carbon fiber couch tops which are optimal for imaging for patient position verification but cause attenuation and increased skin dose compared to the "tennis racket" style couch top they often replace. Also, arc delivery techniques have replaced stationary gantry techniques which cause a greater fraction of the dose to be delivered from posterior angles. A host of immobilization devices are available and used to increase patient positioning reproducibility, and these also have attenuation and skin dose implications which are often ignored. This report of Task Group 176 serves to present a survey of published data that illustrates the magnitude of the dosimetric effects of a wide range of devices external to the patient. The report also provides methods for modeling couch tops in treatment planning systems so the physicist can accurately compute the dosimetric effects for indexed patient treatments. Both photon and proton beams are considered. A discussion on avoidance of high density structures during beam planning is also provided. An important aspect of this report are the recommendations the authors make to clinical physicists, treatment planning system vendors, and device vendors on how to make measurements of surface dose and attenuation and how to report these values. For the vendors, an appeal is made to work together to provide accurate couch top models in planning systems.